Bibliometric Analysis of Studies on Salafism in Indonesia - Nurdiana Abhiyoga; Gonda Yumitro; Shannaz Mutiara Deniar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study analyzes and develops Salafism in Indonesia with a bibliometric approach. In this article, we describe the trend of Salafism publications in Indonesia; (1) Geographical Distribution; (2) Number of Documents Per Author; (3) Number of Documents Per University; (4) Total documents based on the subject area; (5) Documents based on country (6) Indonesian Salafism citation. The authors used the Scopus Search Engine as a tool in data collection in the form of publications related to the theme of Salafism in Indonesia. The data collection using visualization software VOS viewer and Nvivo. The results of this study indicate that, from 2005 to 2021, 68 documents wrote about Salafism in Indonesia in the Scopus database. Indonesia is the country with the most significant contributor to the writing of Salafism in Indonesia as many as 23 documents. Moreover, the highest publications are in social and science journals at 60.8%. When viewed through documents per author, Hasan N is the most author with four documents.